2018
DOI: 10.1002/adsc.201701005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nucleoside Phosphorylases for the Preparation of Purine and Pyrimidine 2′‐Deoxynucleosides

Abstract: Enzymatic transglycosylation – the transfer of the carbohydrate moiety from one heterocyclic base to another – is being actively developed and applied for the synthesis of practically important nucleosides. This reaction is catalyzed by nucleoside phosphorylases (NPs), which are responsible for reversible phosphorolysis of nucleosides to yield the corresponding heterocyclic bases and monosaccharide 1‐phosphates. We found that 7‐methyl‐2′‐deoxyguanosine (7‐Me‐dGuo) is an efficient and novel donor of the 2‐deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…Therefore, the availability of 7-methyl-2 -deoxyguanosine iodide would represent a valuable tool for an alternative synthetic approach, as proven by the bioconversion of Cladribine (see Table 1). However, this sugar donor was found to be less stable than 7-methylguanosine iodide in aqueous medium, in agreement with a very recent report by Mikhailov et al [49]. We have found that this molecule is unstable also in DMSO at room temperature, as indicated from the appearance of extra signals in the 13 C NMR spectrum recorded at two-hour intervals in DMSO, clearly showing that the decomposition of the nucleoside had occurred (see Supplementary Materials, Figure S1).…”
Section: "One-pot One-enzyme" Transglycosylationssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the availability of 7-methyl-2 -deoxyguanosine iodide would represent a valuable tool for an alternative synthetic approach, as proven by the bioconversion of Cladribine (see Table 1). However, this sugar donor was found to be less stable than 7-methylguanosine iodide in aqueous medium, in agreement with a very recent report by Mikhailov et al [49]. We have found that this molecule is unstable also in DMSO at room temperature, as indicated from the appearance of extra signals in the 13 C NMR spectrum recorded at two-hour intervals in DMSO, clearly showing that the decomposition of the nucleoside had occurred (see Supplementary Materials, Figure S1).…”
Section: "One-pot One-enzyme" Transglycosylationssupporting
confidence: 92%
“…While this research was ongoing, an E. coli PNP-catalyzed transglycosylation for the preparation of 2 -deoxynucleosides, including Cladribine, was developed by Mikhailov and co-workers who exploited a 7-methyl purine nucleoside iodide as the sugar donor [49].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this information and the fact that N7-methyl-dGTP has been described to be the major product formed after MMS or iodomethane treatment of dGTP ( 37 , 38 ), we successfully generated N7-methyl-dGTP using this route. The formation of N7-methylated dGTP from iodomethane methylation of dGTP was verified by NMR disclosing the presence of a large H8-proton shift arising when the methylation occurs at the N7 position ( 39 , 40 ) ( Supplementary Figure S3A and B ). By combining HPLC, NMR and LC–MS analysis we could conclude that N7-methyl-dGTP indeed is the major product formed upon MMS treatment of dGTP.…”
Section: Resultsmentioning
confidence: 90%
“…Hydroiodide was obtained according to the literature procedure. [18] (pH 7.5) and 9.9 mL of 50 mM buffer solution of potassium dihydrophosphate at ambient temperature in one portion. The reaction mixture was stirred (orbital shaker) for 5 h at ambient temperature.…”
Section: -Methyl-2′-deoxyguanosinementioning
confidence: 99%